INSTRUMENTAL INDICES ASSOSIATED WITH LEFT VENTRICULAR PREHYPERTROPHY IN YOUNG HEALTHY INDIVIDUALS - Osovska, N.Yu.; Sheremeta, B.V.; Kuzminova, N.V.; Gavriluk, A.O.; Knyazkova, I.I. (World of Medicine and Biology, 2019)
The total of 78 healthy individuals 25.3±0.6 years old were examined. Independent predictors of concentric left ventricular remodeling (prehypertrophy) were determined using multiple linear regression. The most informative predictor in normotensive young people was morning increase rate of arterial blood pressure for more than 14 mm Hg in the presence of which the probability of cardiac remodeling development increases by 9.5 times. Its combination with time index of systolic blood pressure more than 11%, variability of systolic blood pressure more than 8 mm Hg and presence of an abnormal chord in the left ventricle structure increases a chance of concentric remodeling diagnostics by 11-15 times. The use of these parameters in different combinations improves the early diagnostics of heart damage in the absence of complaints and classic criteria for cardiovascular disease diagnosis, primarily masked arterial hypertension.